2018
DOI: 10.1089/neu.2017.5111
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping MicroRNA Expression in Saliva and Cerebrospinal Fluid Accurately Identifies Pediatric Traumatic Brain Injury

Abstract: To assess the accuracy and physiological relevance of circulating microRNA (miRNA) as a biomarker of pediatric concussion, we compared changes in salivary miRNA and cerebrospinal fluid (CSF) miRNA concentrations after childhood traumatic brain injury (TBI). A case-cohort design was used to compare longitudinal miRNA concentrations in CSF of seven children with severe TBI against three controls without TBI. The miRNAs "altered" in CSF were interrogated in saliva of 60 children with mild TBI and compared with 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
99
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 27 publications
6
99
0
Order By: Relevance
“…To our knowledge, two of these three miRNAs have been identified in prior human studies of traumatic brain injury. Our previous study of salivary miRNA among children and adolescents with mild traumatic brain injury identified a 2-fold decrease in miR-28-3p levels compared to healthy peers [ 31 ]. A study of circulating miRNAs among adult patients with chronic hypopituitarism induced by prior severe traumatic injury identified reduced levels of miR-361-5p [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, two of these three miRNAs have been identified in prior human studies of traumatic brain injury. Our previous study of salivary miRNA among children and adolescents with mild traumatic brain injury identified a 2-fold decrease in miR-28-3p levels compared to healthy peers [ 31 ]. A study of circulating miRNAs among adult patients with chronic hypopituitarism induced by prior severe traumatic injury identified reduced levels of miR-361-5p [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that perturbation in miRNA signaling after traumatic brain injury results in overlapping miRNA profiles in cerebrospinal fluid and saliva [ 31 ]. Further, we demonstrated that disruptions in salivary miRNA levels can persist for weeks after initial injury [ 32 ], and predict the occurrence of persistent post-concussive symptoms [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…These brain biomechanical loads initiate a cascade of short-and long-term cellular and sub-cellular biochemical and metabolomic alterations in the brain which cause primary injury and secondary injury that evolves over time [1] and can lead to long-term neurodegeneration [2]. These biochemical and metabolomic alterations first appear in the brain tissue and then, by crossing a number of barriers, manifest in biofluids such as cerebrospinal fluid (CSF), blood, saliva and urine [1][2][3][4][5][6][7][8][9][10][11][12]. Therefore, biofluids contain valuable information about the occurrence and progression of TBI and thus recently have been explored as a source for potential biomarkers to diagnose TBI, as well as to assess its severity, monitor its progression, predict patient outcomes, and determine the effectiveness of therapeutic interventions [1,4,5,[9][10][11][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The anatomic proximity of the perivascular drainage spaces in the glymphatic system to the oropharynx creates a prospective avenue for gut-brain cross-talk and miRNA transfer. 11 In light of the pronounced diurnal activity displayed by the glymphatic system, 38 indirect support for this transfer might lie in the surprising correlations between salivary miRNA levels and time of collection (Table S2, available online). In addition, the mRNA targets of ASD-associated miRNAs show enrichment for circadian-related pathways (Table S4A, available online), which is notable because disordered sleep is a common medical condition in children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, miRNAs can be packaged within exosomes and other lipophilic carriers as a means of extracellular signaling. This feature allows noninvasive measurement of miRNA levels in extracellular biofluids such as saliva 11 and renders them attractive biomarker candidates for disorders of the CNS. 12 Studies of miRNA in children with ASD have demonstrated differential expression patterns in postmortem brain tissue, 13,14 serum, and cultured peripheral lymphoblasts.…”
mentioning
confidence: 99%